Hospital-acquired pneumonia: risk factors and prognosis, microbial etiology, treatment, and prophylaxis - Davide Calabretta; Claudia Accetturo; Antoni Torres (Barcelona Respiratory Network Reviews)
Hospital-acquired pneumonia (HAP) is a group of nosocomial infections that includes a variety of different phenotypes of pneumonia. This heterogeneity, along with the time-dependent nature of the disease, contributes to the difficulty in determining its exact incidence and mortality, despite being one of the most common and lethal hospital acquired infections, particularly in critically ill patients. Many cases of infection are sustained by multi-drug resistant pathogens and require rapid diagnosis and identification of the responsible pathogen and appropriate antibiotic treatment. This review aims to summarize the main evidence in the clinical management of HAP, focusing on the identification of risk factors, prevention, and innovations in the areas of diagnosis and treatment.